Walking between the raindrops: the role of religion in globalised schooling. Issue 5 (3rd September 2021) - Rozenfeld, Itamar; Yemini, Miri; Engel, Laura C.
ABSTRACT: This study applies the notion of 'alternative futures' in globalisation and education by focusing specifically on the intersection between religion and education. Through an in-depth exploration utilising a case-study approach, we delve into the organisational dynamics of an Israeli school catering to a closed-off, traditional Jewish religious community while also proactively embedding specific forms of internationalisation. We identify and analyse the conflicting rationales and agenda maintained by this school based on interviews with the school's community, including teachers, superintendents, school leadership, and parents. We argue that the ideas of segregation, religionalisation, and nationalism are nurtured through the hybridity of the networks of influence, custom-tailored by the school's leadership to serve this unique community. In particular, we analyse the school's distinctive practices, norms, and routines designed to overcome the gap between the seemingly contradictory values of universalism vs particularity; globalisation vs nationalism; segregation vs unity; and religion vs modernity, and the ways that these dynamics play out in a country struggling for (self)-recognition as a Jewish and Democratic State, while being situated in an intractable internal and external conflict.